2010
DOI: 10.7326/0003-4819-152-2-201001190-00006
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescriptions for Chronic Pain and Overdose

Abstract: Background Chronic opioid therapy for chronic non-cancer pain (CNCP) is increasingly common in community practice. Concomitant with this practice change, rates of fatal opioid overdose have increased. It is not known to what extent overdose risks are elevated among patients receiving medically prescribed chronic opioid therapy. Objective To estimate rates of opioid overdose and their association with average prescribed daily opioid dose among patients receiving medically prescribed chronic opioid therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
960
7
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,136 publications
(1,019 citation statements)
references
References 31 publications
29
960
7
6
Order By: Relevance
“…[25][26][27][28] Consistent with existing literature on the misuse of prescription drugs, we found that patients who had a psychiatrist in the care team were more likely to be exposed to multiple-provider prescriptions of benzodiazepines. 25,26 In-depth analysis of care team composition revealed that a significant proportion of patients who received benzodiazepine from a psychiatrist had a concurrent benzodiazepine prescription from a different provider (Table 3), signifying the need for greater care in treating and monitoring these patients. Patients with psychiatric illness often present with other medical conditions; the need for an integrated care approach that promotes collaboration among psychiatrists, PCPs, and other medical professionals caring for these patients is well recognized.…”
Section: Discussionsupporting
confidence: 77%
“…[25][26][27][28] Consistent with existing literature on the misuse of prescription drugs, we found that patients who had a psychiatrist in the care team were more likely to be exposed to multiple-provider prescriptions of benzodiazepines. 25,26 In-depth analysis of care team composition revealed that a significant proportion of patients who received benzodiazepine from a psychiatrist had a concurrent benzodiazepine prescription from a different provider (Table 3), signifying the need for greater care in treating and monitoring these patients. Patients with psychiatric illness often present with other medical conditions; the need for an integrated care approach that promotes collaboration among psychiatrists, PCPs, and other medical professionals caring for these patients is well recognized.…”
Section: Discussionsupporting
confidence: 77%
“…5,6 Although there is a rich historical literature on the demographics and event-level characteristics of heroin overdose, 7,8 our understanding of recent trends of opioid overdose is limited and largely based on health system and non-urban regional analyses. [9][10][11][12][13][14] Prescription opioid overdose has been documented among rural and suburban non-Hispanic white men, [9][10][11][12][13][14][15] middle-aged females, 16,17 and those using psychotherapeutic drugs. 2,18 Patients in safety net healthcare systems, including the Veterans Administration 19 and Medicaid, 20 are more likely to die of prescription opioid overdose compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…We examined five categories for the mean daily MED (i.e., 0, 1-19, 20-49, 50-99, and ≥100 mg), similar to other studies. 9,10 For the first overdose, the mean daily MED was based on data from exactly 6 months before that event (Fig. 2).…”
Section: Study Settingmentioning
confidence: 99%